2021
DOI: 10.1111/ene.15164
|View full text |Cite
|
Sign up to set email alerts
|

circSKA3 acts as a sponge of miR‐6796‐5p to be associated with outcomes of ischemic stroke by regulating matrix metalloproteinase 9 expression

Abstract: Background and purpose This study was undertaken to screen the circular RNAs (circRNAs) influencing matrix metalloproteinase 9 (MMP9) through the competing endogenous RNA (ceRNA) network and evaluate the prognostic value of these circRNAs for acute ischemic stroke. Methods A total of 220 ischemic stroke patients and 62 healthy subjects were included in this study. RNA was isolated from blood collected in PAXgene tubes. Illumina sequencing, quantitative real‐time polymerase chain reaction (qRT‐PCR) validation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The crosstalk between circRNA, miRNA, and mRNA (or proteins) through one or more circRNA–miRNA–mRNA networks indicates the complicated and dynamic mechanisms of brain cognitive disorders including AD (Zhao et al, 2016 ; Lu et al, 2019 ; Yang et al, 2019 ; Zhu et al, 2020 ; Li et al, 2022 ; Pan et al, 2022 ; Xu X. et al, 2022 ), PD (Kumar et al, 2018 ; Feng et al, 2020 ; Wang et al, 2021 ; Liu et al, 2022 ; Zhang et al, 2022 ), TBI (Chen et al, 2019 ; Li H. et al, 2020 ; Huang X. J. et al, 2022 ; Zheng et al, 2022 ), stroke (Bai et al, 2018 ; Han et al, 2018 ; Zhou et al, 2021 ; Guo et al, 2022 ; Huang et al, 2022 ; Xu T. et al, 2022 ; Yang H. et al, 2022 ; Yang J. et al, 2022 ), and POND (Gao et al, 2020 ) ( Table 1 ). In summary, circRNAs act as sponging-like roles in transcription and posttranscription in the novel regulation processes of gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crosstalk between circRNA, miRNA, and mRNA (or proteins) through one or more circRNA–miRNA–mRNA networks indicates the complicated and dynamic mechanisms of brain cognitive disorders including AD (Zhao et al, 2016 ; Lu et al, 2019 ; Yang et al, 2019 ; Zhu et al, 2020 ; Li et al, 2022 ; Pan et al, 2022 ; Xu X. et al, 2022 ), PD (Kumar et al, 2018 ; Feng et al, 2020 ; Wang et al, 2021 ; Liu et al, 2022 ; Zhang et al, 2022 ), TBI (Chen et al, 2019 ; Li H. et al, 2020 ; Huang X. J. et al, 2022 ; Zheng et al, 2022 ), stroke (Bai et al, 2018 ; Han et al, 2018 ; Zhou et al, 2021 ; Guo et al, 2022 ; Huang et al, 2022 ; Xu T. et al, 2022 ; Yang H. et al, 2022 ; Yang J. et al, 2022 ), and POND (Gao et al, 2020 ) ( Table 1 ). In summary, circRNAs act as sponging-like roles in transcription and posttranscription in the novel regulation processes of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of circ_0000831 is sufficient to inhibit neuroinflammation and vertigo in cerebral ischemia through a miR-16-5p-dependent mechanism (Huang et al, 2022 ). circSKA3, in an area under the ROC curve of 0.614 (95% CI: 0.546–0.680) in predicting clinical outcomes of patients with AIS, acts as a sponge of miR-6796-5p by regulating the expression of matrix metalloproteinase 9 (Xu T. et al, 2022 ). Hypoxic pretreated adipose-derived stem cell (ADSC) exosome improves cognitive function by decreasing neuronal damage and shifting microglia from an M1 to M2 phenotype in the hippocampus of AIS via circRps5/miR-124-3p/SIRT7 axes (Yang H. et al, 2022 ).…”
Section: Circrna–mirna–mrna Network In Brain Cognitive Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Circ cGLIS3 ( 46 ), circRNA TLK1 ( 136 ), circPHC3 ( 45 ), circFUNDC1 ( 44 ), and circCDC14A ( 43 ) contribute to cell death by activating apoptosis. Overexpression of circ HIPK2 ( 56 ) and circSKA3 ( 137 ) aggravates neuronal injuries.…”
Section: The Role Of Circrnas As Biomarkers and Therapeutic Targets I...mentioning
confidence: 99%
“…A recent study reported that hsa_circ_0045932 (circUSP36) attenuates ischemic stroke injury through the miR-139-3p/SMAD3/Bcl2 signaling axis ( 19 ). Xu et al ( 20 ) revealed that circSKA3 could compete for binding hsa-miR-6796-5p and thereby regulates MMP9 to promote ischemic stroke progression. However, there remain numerous dysregulated circRNAs whose roles in IS have not been reported.…”
Section: Introductionmentioning
confidence: 99%